2015
DOI: 10.1103/physrevb.92.155424
|View full text |Cite
|
Sign up to set email alerts
|

Photogalvanic effect in the HgTe/CdTe topological insulator due to edge-bulk optical transitions

Abstract: We study theoretically 2D HgTe/CdTe quantum well topological insulator (TI) illuminated by circularly polarized light with frequencies higher than the difference between the equilibrium Fermi level and the bottom of the conduction band (THz range). We show that electron-hole asymmetry results in spin-dependent electric dipole transitions between edge and bulk states, and we predict an occurrence of a circular photocurrent. If the edge state is tunnel-coupled to a conductor, then the photocurrent can be detecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
50
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 35 publications
0
50
0
4
Order By: Relevance
“…There have been many theoretical and experimental works in the past few years on helicity-controlled photocurrents [14][15][16][17][18], the linear photogalvanic effect [19][20][21], local photocurrents [22,23], edge photocurrents in two-dimensional (2D) TIs [24,25], coherent control of injection currents [26,27], photon drag currents [19,28,29], second-harmonic generation [30], photoinduced quantum Hall insulators [31,32], cyclotron-resonance-assisted photocurrents [33,34], quantum oscillations of photocurrents [35], photogalvanic currents via proximity interactions with magnetic materials [36][37][38], and the photoelectromagnetic effect [39]. These phenomena, scaling in the second or third order of the radiation electric fields, open up new opportunities to study Dirac fermions, which has been already demonstrated for graphene (for a review see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many theoretical and experimental works in the past few years on helicity-controlled photocurrents [14][15][16][17][18], the linear photogalvanic effect [19][20][21], local photocurrents [22,23], edge photocurrents in two-dimensional (2D) TIs [24,25], coherent control of injection currents [26,27], photon drag currents [19,28,29], second-harmonic generation [30], photoinduced quantum Hall insulators [31,32], cyclotron-resonance-assisted photocurrents [33,34], quantum oscillations of photocurrents [35], photogalvanic currents via proximity interactions with magnetic materials [36][37][38], and the photoelectromagnetic effect [39]. These phenomena, scaling in the second or third order of the radiation electric fields, open up new opportunities to study Dirac fermions, which has been already demonstrated for graphene (for a review see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Photocurrents caused by the Drude-like free-carrier absorption require additional scattering and k-dependent velocity and, therefore, seem to be weak. Comparing the efficiencies of all these processes we attribute the circular edge photocurrents in region II to the excitation of electrons from helical edge states to bulk conduction band states ("photoionization" of the edge channels) [29,30].…”
mentioning
confidence: 99%
“…[24]). In a simple four-subband model with inversion center, the coefficient K at k x = 0 is given by 2BD/(B 2 + D 2 ) [29], where B and D are the parameters of the Bernevig-Hughes-Zhang (BHZ) Hamiltonian [2]. PHYSICAL Calculations within the relaxation time approximation yield the following expression for the edge current:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In various semiconductor systems, such as lowdimensional structures of GaAs, InAs, SiGe, GaN and ZnO, CPGE has been successfully used as a tool to determine the relative ratio of Rashba and Dresselhaus terms (RD ratio) [23][24][25][26][27][28][29] . Because of the unique SOI property and novel TI phase of HgTe QWs, CPGE in HgTe QWs has also attracted considerable interest [30][31][32] . Experimentally, large CPGE signals in (001)-and (113)-oriented HgTe QWs have been observed in terahertz and mid-infrared regions 30,31 , and have found their application in the fast detection of the infrared-radiation ellipticity 15,16 .…”
Section: Introductionmentioning
confidence: 99%